Missed opportunities for catch-up human papillomavirus vaccination among university undergraduates: Identifying health decision-making behaviors and uptake barriers. Issue 2 (4th January 2018) - Ragan, Kathleen R.; Bednarczyk, Robert A.; Butler, Scott M.; Omer, Saad B.
Highlights: Despite recommendations, HPV vaccine coverage rates remain low among adolescents. Little is known about influencing factors in young adults' vaccine decision making. College students' vaccine decision making is largely influenced by their parents. Catch-up strategies are needed to increase students' control over decision making. Interventions addressing parental barriers can increase students' vaccine uptake. Abstract: Background: Suboptimal adolescent human papillomavirus (HPV) vaccine rates in the US highlight the need for catch-up vaccination. When teenagers enter college, there may be a shift in healthcare decision-making from parents and guardians to the students themselves. Little is known about factors influencing college students' healthcare decision-making processes. Study design: We evaluated HPV vaccine decision-making among 18-to-26-year-old college students through a self-administered, anonymous, cross-sectional survey. This survey was distributed to a sample of men and women in classroom settings at two universities. Categorical data comparisons were conducted using Chi-square and Fisher's exact tests. Multivariate Poisson regression was used to model initiation of HPV vaccine and compute prevalence ratios while controlling for key influential covariates at the 0.05 alpha level. Results: A total of 527 students participated (response proportion = 93.1%). Overall, 55.8% of participants received the HPV vaccine. Encouraging conversations with doctors and/or parents/guardians were identified as one of the most influential factors to increase vaccine uptake. Among students who received encouragement from both a doctor and parent, 95.8% received the vaccine. Campaigns about cancer prevention were viewed as more influential than those that focus on preventing genital warts. Approximately one-third of students indicated they didn't know where to get the HPV vaccine. Women were more likely to report that their parents would not let them get the HPV vaccine compared to men (26.7% vs. 2.3%). The majority of students (77.3%) indicated their parents were sometimes, equally, or mostly involved in making decisions about receiving vaccines (other than flu). Conclusion: Students' decision-making is greatly influenced by their parents; therefore, interventions for this population should work to increase students' control over decision-making while also addressing parental concerns.